Mouse Models for Human Skin Transplantation: A Systematic Review - Cristóbal, Lara; Asúnsolo, Ángel; Sánchez, Jorge; Ortega, Miguel A; Álvarez-Mon, Melchor; García-Honduvilla, Natalio; Buján, Julia; Maldonado, Andrés A (Cells, tissues, organs, 2021)
Immunodeficient mouse models with human skin xenografts have been developed in the past decades to study different conditions of the skin. Features such as follow-up period and size of the graft are of different relevance depending on the purpose of an investigation. The aim of this study is to analyze the different mouse models grafted with human skin. A systematic review of the literature was performed in line with the PRISMA statement using MEDLINE/PubMed databases from January 1970 to June 2020. Articles describing human skin grafted onto mice were included. Animal models other than mice, skin substitutes, bioengineered skin, postmortem or fetal skin, and duplicated studies were excluded. The mouse strain, origin of human skin, graft dimensions, follow-up of the skin graft, and goals of the study were analyzed. Ninety-one models were included in the final review. Five different applications were found: physiology of the skin (25 models, mean human skin graft size 1.43 cm2 and follow-up 72.92 days), immunology and graft rejection (17 models, mean human skin graft size 1.34 cm2 and follow-up 86 days), carcinogenesis (9 models, mean human skin graft size 1.98 cm2 and follow-up 253 days), skin diseases (25 models, mean human skin graft size 1.55 cm2 and follow-up 86.48 days), and would healing/scars (15 models, mean human skin graft size 2.54 cm2 and follow-up 129 days). The follow-up period was longer in carcinogenesis models (253 ± 233.73 days), and the skin graft size was bigger in wound healing applications (2.54 ± 3.08 cm2). Depending on the research application, different models are suggested. Careful consideration regarding graft size, follow-up, immunosuppression, and costs should be analyzed and compared before choosing any of these mouse models. To our knowledge, this is the first systematic review of mouse models with human skin transplantation.